A Comprehensive Systematic Review of The Relationship between Benzodiazepine Use and Psychomotor Impairment - Arfin Ramadhan; Nur Shella Putri B; Reni Margiyanti Adiningsih (International Medical Journal Corp. Ltd, 2026)
Introduction: Benzodiazepines (BZDs) are widely prescribed for anxiety and insomnia, but their impact on psychomotor function is a significant safety concern. This review synthesizes evidence from 41 studies on the association between BZD use and psychomotor impairment. Methods: A comprehensive review of 41 sources was conducted. Data were extracted on BZD details (type, dose, duration), psychomotor outcomes (reaction time, motor function, driving, falls), and relationship findings. Results: The evidence consistently demonstrates BZD-associated psychomotor impairment. Meta-analyses show a 60% increased risk of motor vehicle collisions (OR=1.60) and a 34% increased risk of hip fractures (RR=1.34) among users (1,2). An experimental study confirmed acute impairment in reaction time and tracking accuracy lasting up to 14.5 hours (3). Dose-response relationships were observed, with high-dose users (>1 DDD) showing significantly prolonged reaction times (4) and a fourfold increased fall risk (8). Chronic use was linked to neurocognitive impairment in vulnerable populations like people living with HIV (OR=2.13) (5) and executive function deficits (6). Elderly populations were identified as most at risk for falls and functional decline (2,7,10-12). Discussion: The findings converge on a pattern of impairment across multiple psychomotor domains. While most studies show significant effects, one study in psychogeriatric patients found no cognitive decrements, likely due to confounding by indication where the comparison group was already compromised (9). The synthesis reveals that effects are more pronounced with higher doses, current use, longer-acting agents, and in elderly populations. Conclusion: Benzodiazepine use is significantly associated with impaired psychomotor function, including prolonged reaction time, impaired driving, and increased risk of falls and fractures. These risks are dose-dependent and more severe in vulnerable populations, particularly the elderly. Clinicians should carefully weigh these risks, prescribe at the lowest effective dose for the shortest duration, and exercise special caution in high-risk groups. Further research should focus on standardized outcome measures and long-term prospective studies in diverse populations.